The Effect of Lubricant on the Detorque Force of Locator/Kerator Abutment in Overdenture Patients: A Pilot Clinical Study - Ali Chamani; ِِDavood Aghasizadeh; Hamidreza Rajati Haghi; Ghazal Aghebati; Reza Shakiba (Journal of Dentistry)
Background: Despite the implants' remarkable success, mechanical failure of implant-abutment screws is a challenge for clinicians. Among the types of mechanical failures, abutment screw loosening is still frequently reported in the literaturePurpose: The present study aimed to evaluate the effect of using lubricant on the detorque force (removal force) of locator/kerator abutment in overdenture patients after 6 months of clinical usage.Materials and Method: This pilot clinical study examined the detorque force of implants in 20 edentulous patients with two mandibular implants positioned between the mental foramen. The patients underwent the fabrication of a complete maxillary prosthesis and mandibular overdenture. Before loading attachments in the delivery session, healing abutments were removed, and implant interiors dried, randomly some fixtures received a tetracycline eye ointment 1% lubricant, while the others remained non-lubricated. Abutments were secured with prescribed torque according to implant system guidelines (20 N.cm). After 6 months, detorque forces for the abutment locators were measured using a torque meter. Descriptive statistics, mean comparison, and Pearson correlation were performed on the obtained data. A significant level of P<0.05 was considered in the present study.Results: The mean detorque force was 13.4±1.94 in the non-lubricated group and 16.35± 1.24 in the lubricated group, which was significantly higher in the lubricated group (p< 0.001). Other results of the study include the non-significance of the difference in detorque force within male and female groups (p> 0.05), as well as the non-significance of Pearson's correlation between patients' age and detorque force (p> 0.05).Conclusion: According to the results, the use of lubricant significantly increases the detorque force, and it is recommended to use tetracycline eye ointment as a lubricant in implant treatment processes.